2014
DOI: 10.1177/0734282913514351
|View full text |Cite
|
Sign up to set email alerts
|

VMI-VI and BG-II KOPPITZ-2 for Youth With HFASDs and Typical Youth

Abstract: The visual-motor skills of 90 youth with high-functioning autism spectrum disorders (HFASDs) and 51 typically developing (TD) youth were assessed using the Beery-Buktenica Developmental Test of Visual-Motor Integration, Sixth Edition (VMI-VI) and Koppitz Developmental Scoring System for the Bender-Gestalt Test-Second Edition (KOPPITZ-2). Within-group comparisons (for both samples) yielded substantive mean differences between the KOPPITZ-2 composite and VMI-VI composite, Visual Perception and Motor Coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For the purpose of this study the term visual-motor performance 7 refers to these motor enhanced sub-tests, such as visual-motor integration, visual-motor speed, and eye-hand coordination. The term visual-motor performance is used interchangeably in the literature with visual-motor functions, and visual motor skills 27 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the purpose of this study the term visual-motor performance 7 refers to these motor enhanced sub-tests, such as visual-motor integration, visual-motor speed, and eye-hand coordination. The term visual-motor performance is used interchangeably in the literature with visual-motor functions, and visual motor skills 27 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Those that wore corrective lenses for minor visual acuity problems were monitored to ensure they used their corrective lenses during all screening testing and the current experiments. Earlier studies of HF children with ASD found no significant differences in visual perceptual acuity from that of TD children ( Volker et al, 2010 ; McDonald et al, 2014 ). Ten of the HF children with ASD and 10 matched TD children from Situation A also participated in the Church et al (2010) experiment, and thus had some past experience with the general task, though not with the particular categories, stimuli, and training specifics experienced in this context.…”
Section: Methodsmentioning
confidence: 70%
“…The perceived challenge may reflect objective difficulties experienced by the child. Previous studies have recognized the motor, cognitive, and social deficiencies of children with NDD (Mattard-Labrecque et al, 2013;McDonald et al, 2014). Hence, taking part in everyday activities such as dressing, organizing one's room, doing homework, or playing with friends may not be easy.…”
Section: Discussionmentioning
confidence: 99%